LAPTOP SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF BERBASIS TEKNOLOGI INFORMASI DI SEKOLAH DASAR - Nisrina Nisrina; Yeni Puspitasari; Mawaddha Mawaddha (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Along with the progress of the times, the application of modern technology and the present is increasingly being promoted in various sectors of life, including in the world of education. The use of media in the learning process is one of the efforts to create more meaningful and quality learning. One of the most advanced and widely used technologies today is laptops. The use of laptops in learning is widely used, but in its application there are not many teachers who understand and utilize these technologies. Laptops as information technology and interactive learning media are able to make students more active, creative, fun learning, not boring and increase students' interest in learning.